International survival and strategic renewal through disrupting path dependence - Rossato, Gabrielle Damo; Floriani, Dinorá Eliete; Amal, Mohamed (Revista Eletrônica de Administração, 2023)
The aim of the present article is to analyze how firms can strategically renew themselves and disrupt their path dependence to survive in international markets, despite the influence of path dependence. Using a qualitative methodology, this study has adopted a single-case design, based on semi-structured interviews with employees involved in the path of an emerging market firm. Through a historic and process-driven analysis it was possible to use realtime and retrospective data. The paper leads to the start of debates about path dependence transition. It also presents the relationship between international survival, strategic renewal and path dependence disruption.